LANGUAGE MAINTENANCE OF JAVANESE TEENAGERS AT DESA PAMUKTARAN - Prima . Yanti; Rahmad . Husein; Didik . Santoso (LINGUISTIK TERAPAN, 2021)
This study deals with the language maintenance of Javanese teenagers of Desa Pamuktaran preserve. It uses qualitative research design with a single case study to gain an understanding on this study. It is conducted descriptively. This study aims to desescribe what language maintenance do the Javanese people of Desa Pamuktaran preserve. The subjects were 15 participants of the third generations that have selected as the source of data in this study. The use of instruments in this study were observation,interview and documentation. The observation were used desescribe what language maintenance do the Javanese people of Desa Pamuktaran preserve. The interview was used in depth data. The theories of Fasold, Fishman and Holmes are used in this study. The data were analyzed Miles and Huberman and Saldana’s technique. The data from questionnaire will be analyzed by using the following steps; (1) data reduction, (2) data display, (3) verification and drawing conclusion. There are four types of language maintenance of Javanese language in Desa Pamuktaran they are low maintenance, medium maintenance, strong maintenance and extreme maintenance.Keywords: Language Maintenance, Javanese, Teenagers, Javanese Language